The Photoelectric Instrument at the Bosscha Observatory - Santoso Nitisastro (Journal of Mathematical and Fundamental Sciences, 1963)
Ichtisar. Sebuah uraian tentang pesawat ptotoelectris photometer di Observatorium Bosscha Lembang, dengan mempergunakan sebuh photomultiplier type 1P21 jang didinginkan dengan es kering atau sebuah multiplier type EMI pada pendinginan telah disadjikan dibawah ini. Photometer tersebut jang diperlengkapi dengan filter2 U, B, V dan R, dipasangkan pada teropong lensa 37 cm Bamberg-Schmidt dan baru dapat dipergunakan untuk menentukan ekstingsi atmosfir untuk Observatorium Bosscha di Lembang pada penghabisan musim terang dalam tahun 1962.Abstract. A description of the photoelectric photometer at the Bosscha Observatory Lembang, operated with a photomultiplier of type IP21 refrigerated with dry ice  or using an EMI-type of multiplier (non-refrigerated) is presented below. The photometer, provided with U, B, V, and R filters and attached to the 37 cm Bamberg-Schmidt refractor, has been used for determining the atmospheric extinction of the Observatory during the last part of the dr season in 1962.